Development of 3D Animated Video Learning Media for Recognizing Alphabet Letters at the At-Taqwa Playgroup in Pajar Bulan Village, Ogan Ilir Regency - Sari, Dea Kartika; Saputra, Ardi; Safitri, Erna Retna (Universitas Pahlawan Tuanku Tambusai, 2026)
Early childhood education in non-formal playgroups such as At-Taqwa in Pajar Bulan Village, Ogan Ilir Regency, faces challenges in introducing the alphabet due to boring print media even though audiovisual facilities are available, causing low interest in learning and suboptimal literacy development. This study aims to develop valid and practical 3D animated video learning media for introducing the alphabet for early childhood. Using research and development (RD) with the ADDIE model (analysis, design, development, implementation), a population of 41 children with one-to-one (3 children) and small group (10 children) trial samples. Instruments include a Likert Scale expert validation questionnaire, a Guttman Scale practicality questionnaire, interviews, and observations; data analysis using a percentage formula. The results show high validity (average 90.83%: material 90%, media 87.5%, language 95%) and practicality (100% in both trials). In conclusion, the media is effective in increasing interest in learning and mastery of the alphabet, ready to be implemented in PAUD.